Pelaksanaan Pelayanan Kunjungan Berbasis Information Technology (IT) - Dzikrulloh, Bakti (Jurnal Analisis Sosial Politik, 2022)
Visiting servants are part of the public services carried out in correctional institutions throughout Indonesia. In a time of increasingly rapid development in line with the development of increasingly advanced technology public services carried out have a great influence, especially in information technology-based visitation services. As a result, the development of information technology is applied to service visits to correctional institutions to improve service quality. This research will raise the issue of how the implementation of information technology (IT) based visit services. This study aims to determine the implementation of a visit based on information technology (IT) in. This research was conducted in Correctional Institution Class IIA in Kerobokan. This research uses a qualitative research approach. Data collected by observation, interview and document study techniques are then processed and analyzed qualitatively. The results of this study indicate that the Correctional Institution Class IIA in Kerobokan uses IT advancements in conducting visits. this can also be seen from the amount of visitor satisfaction given to the Class IIA prison in Kerobokan.